2018
DOI: 10.1128/mbio.01345-18
|View full text |Cite
|
Sign up to set email alerts
|

Late Endosomal/Lysosomal Cholesterol Accumulation Is a Host Cell-Protective Mechanism Inhibiting Endosomal Escape of Influenza A Virus

Abstract: To transfer the viral genome into the host cell cytoplasm, internalized influenza A virus (IAV) particles depend on the fusion of the IAV envelope with host endosomal membranes. The antiviral host interferon (IFN) response includes the upregulation of interferon-induced transmembrane protein 3 (IFITM3), which inhibits the release of the viral content into the cytosol. Although IFITM3 induction occurs concomitantly with late endosomal/lysosomal (LE/L) cholesterol accumulation, the functional significance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 50 publications
7
82
2
Order By: Relevance
“…Because the pronounced decrease in SARS-CoV-2 titers observed upon treatment with U18666A hinted at an antiviral capacity of dysregulated endolysosomal cholesterol contents in SARS-CoV-2 infection, we next determined whether fluoxetine treatment of Vero and Calu-3 cells was associated with increased endolysosomal cholesterol pools. We acquired z-stacks from confocal microscopy using CD63 as the specific endolysosomal marker protein (20) (12,13). In line with the images, this quantitative colocalization analysis ( Fig 2B), revealed that fluoxetine at a low concentration of 5 µM caused slightly, yet not significantly elevated cholesterol levels in CD63-positive LELs, whereas treatment with 20 µM fluoxetine induced a prominent and significant endolysosomal cholesterol accumulation.…”
Section: Fluoxetine Treatment Is Associated With Increased Endolysososupporting
confidence: 62%
See 2 more Smart Citations
“…Because the pronounced decrease in SARS-CoV-2 titers observed upon treatment with U18666A hinted at an antiviral capacity of dysregulated endolysosomal cholesterol contents in SARS-CoV-2 infection, we next determined whether fluoxetine treatment of Vero and Calu-3 cells was associated with increased endolysosomal cholesterol pools. We acquired z-stacks from confocal microscopy using CD63 as the specific endolysosomal marker protein (20) (12,13). In line with the images, this quantitative colocalization analysis ( Fig 2B), revealed that fluoxetine at a low concentration of 5 µM caused slightly, yet not significantly elevated cholesterol levels in CD63-positive LELs, whereas treatment with 20 µM fluoxetine induced a prominent and significant endolysosomal cholesterol accumulation.…”
Section: Fluoxetine Treatment Is Associated With Increased Endolysososupporting
confidence: 62%
“…Because our previously published results had revealed that increased endolysosomal cholesterol levels act as an effective antiviral barrier for enveloped viruses, including influenza viruses (12)(13)(14)19), we also tested the impact of a post-infection treatment with U18666A, a small molecule inhibitor of the endolysosomal cholesterol transporter NPC1(17) on SARS-CoV-2 infection. As shown in Fig.…”
Section: Fluoxetine Treatment Impairs Sars-cov-2 Infection In Calu-3 mentioning
confidence: 99%
See 1 more Smart Citation
“…Although IFN-I-induced lysosomal acidification sensitizes cells to an intracellular bacterial pathogen, our finding that several known ISGs with antiviral properties, such as Ifitm3, Slc15a3 and Cnp , participate in this process leads us to speculate that this mechanism may be protective against viral threats. IFN-I-mediated lysosomal remodeling may also play a role in non-infectious pathologies, such as lysosomal cholesterol accumulation (Kuhnl et al, 2018) and other lysosome-related disorders. It remains unclear whether these effects might be driven by the tonic IFN-I signaling that occurs in many tissues (Schoggins et al, 2014), or instead require pathogenic elevations of IFN-I.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally IFITM3 binds to vesicle-associated membrane proteinassociated protein A (VAPA), a master regulator of endosome-ER lipid transport and alters endosomal cholesterol levels to inhibit virus entry [300]. Further research has shown that cholesterol accumulates in the late endosome upon IFITM3 expression [274,309].…”
Section: Ifitm3 Restricts Infection By Several Different Virusesmentioning
confidence: 99%